Generic ICD programming and outcomes. Issue 12 (2nd November 2021) - Khan, Parisha; Jahagirdar, Nishat; Laybourn, Micaela; Harding, Idris; Cannatà, Antonio; Bromage, Daniel I.; Shabeeh, Husain; Kabunga, Peter; Petzer, Edward; Murgatroyd, Francis; Scott, Paul A.
Abstract: Introduction: Generic ICD programming, where shock‐reduction programming is extrapolated from trials of one manufacturer to another, may reduce non‐essential ICD therapies beyond that seen in randomized trials. However, the benefits and risks are unknown. The purpose of this retrospective cohort study was to evaluate the impact of a standardized programming protocol, based on generic programming, across manufacturers. Methods: We included all new ICDs in a single center (2009–2019). In 2013 a standardized programming protocol based on generic programming was introduced, incorporating high detection rates (200 bpm for primary prevention) and long detection (30/40 or equivalent in VF zone) for all patients. Patients were classified into three groups based on implant programming: pre‐guideline (PS), post‐guideline and guideline compliant (GC) and post‐guideline but not guideline compliant (NGC). The end‐points were the first occurrence of any device therapy (ATP or shock), ICD shock, syncope and all‐cause mortality. Survival analysis was used to evaluate outcomes. Results: 1003 patients were included (mean follow‐up 1519 ± 1005 days). In primary prevention patients ( n  = 583) freedom from ICD therapy (91.5% vs. 73.6%, p  < .001) or shock (94.7% vs 84.8%, p  = .02) were significantly higher in GC compared to PS patients, without significant increase in syncope or mortality. In secondary prevention patients ( n  = 420) freedom from any ICD therapy or any shock were non‐significantly higher in GC compared to PS patients, without an increase in syncope or mortality. Conclusions: In primary prevention patients a standardized programming protocol, incorporating generic programming, reduced the burden of ICD therapy without an increase in adverse outcomes.